Human capital development in South Asia achievements, prospects, and policy challenges. (Metro Manila, Philippines Asian Development Bank, 2017)
Human capital is an important factor for economic growth in South Asia. Between 1981 and 2010, human capital contributed about 22% of annual gross domestic product per worker growth in India. During the same period, it contributed around 21% in Bangladesh, and 16% in Sri Lanka. However, education and skills remain the binding constraint. Raising the quality of education and skills in South Asia workforce can play a critical role in catching up to the level of development of the People Republic of China, the Republic of Korea, and other successful Southeast Asian economies.
Keywords: Teaching education -- Economic aspects; Electronic books